ANALISIS PENGARUH HARDBALL STRATEGI (DESAIN PRODUK, TAGLINE DAN PESAN IKLAN) TERHADAP KEPUTUSAN PEMBELIAN ADES DI KABUPATEN JEMBER - Amalia, Cinthia Dwi; Azhad, Muhammad Naely; Rahayu, Jekti (Growth, 2024)
This research aims to determine the influence of product design, taglines and advertising messages as hardball strategies on purchasing decisions for Ades Jember drinking water. This type of research is quantitative. The population in this study were all Ades drinking water consumers in Jember using the Ferdinand formula sampling technique. The data source in this research uses primary data, namely questionnaires. Data were analyzed using multiple linear regression, normality test, multicollinearity test, heteroscedasticity test, t test, f test, and determination test which were carried out computationally with the SPSS program. The results of this research show that product design, taglines and advertising messages have a positive and significant effect on purchasing decisions for Ades Jember drinking water.